Education Scorecard in the Middle East Performance and Context into Student Achievement in Global Tests - BouJaoude, Saouma; Faour, Muhammad (Springer Nature Switzerland : Imprint: Springer, 2024)
LVI, 324 p. 218 illus., 217 illus. in color.